Leadership Roles in Medical Academia: Qualification, Experience, Administration, or Research? - Omer, Wafa; Umar, Muhammad (Journal of Rawalpindi Medical College, 2026)
Medical academic excellence is based on leadership. This is because the appointments of department heads, deans, senior faculty administrators, and faculty members directly impact the quality of teaching and faculty motivation. A fundamental question is unanswered in Pakistan: what truly qualifies individuals to lead - higher academic qualification or experience? What about administrative abilities and research accomplishments? A Case for Qualifications and Competencies Beyond Years of Experience In some institutions, the majority of leadership positions are still awarded on the basis of chronological seniority and length of service. This is often done without taking into consideration academic qualifications or leadership capabilities. Years of service are equated with expertise in this long-standing, but flawed practice. The time spent at a job does not translate into a productive contribution. Many individuals have accumulated years with no measurable contribution to academic or scientific research, innovative teaching methods, or roles in institutional leadership. The higher the qualifications, whether it’s a doctorate, a specialized fellowship, advanced training in health administration, medical research, education methodology, or research, then, the more likely you are to have the ability and capacity for transformative leadership. The expectation is that academic leaders will not just serve, but achieve have producing impactful work, obtaining grants, mentoring and supporting younger faculty, or representing their institution within scholarly communities. It is far more beneficial for an institution to have leadership that focuses on academic depth and excellence. Integrating Administrative and Research Competence Leadership is not possible without administrative expertise and research involvement. The ability to effectively manage academic teams and handle complex academic systems is essential for effective governance. Leadership with advanced degrees but without managerial skills may have difficulty implementing policies, and an administrator who lacks academic background or research knowledge risks turning academia into bureaucracy. The ideal leader of medical education should be an academically qualified, administratively skilled, ethically grounded professional with a strong research focus. PM&DC Needs to Define Standards It is critical that Pakistani medical educators fill the gap of a lack of nationally recognized criteria to determine academic leadership. Pakistan Medical and Dental Council’s (PM&DC) role in setting leadership criteria must be based more on documented contribution and demonstrated expertise than just job longevity. Key policy recommendations include the following: Benchmarks for mandatory higher education (e.g., PhD or FCPS certification, or the equivalent advanced certification), required of Deans. Principals and Directors There are weighting systems that give more importance to research, postgraduate supervision, or scholarly output than simple seniority. Processes of selection transparently incorporating peer-review, academic audit, leadership interviews, etc. Continuous professional growth in academic leadership and healthcare administration with requirements for revalidation, impactful, research-based publications, not just the quantity of publications. The succession planning process identifies future leaders and prepares them based solely on performance and merit. Conclusion It is a common practice to confuse "years" of service with "experience". The result has been a decline in leadership standards across medical institutions. Academic leadership requires not only tenure but advanced knowledge, intellectual rigor, and a vision for transformation. For Pakistan to raise the quality and credibility of its medical system, it must switch from a time-based selection to a qualification-based and competence-based meritocracy. PM&DC is both mandated and obligated to implement these standards in order to ensure that the leadership of medical academia goes to the most competent individuals who can advance education, professional ethics, and research. Leadership isn’t measured by the number of years you have served. It’s about impact, and this can only be achieved by a higher-level qualification.